The Effect of Grhasia Sadewa on the Response Time of Requests for People with Mental Disorders Evacuation at Grhasia Hospital Yogyakarta - Sudiharja Sudiharja; Priyanta Nugraha; Hadi Pramono (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background: The prevalence of severe mental disorders in Indonesia have increased, as well as in the Special Region of Yogyakarta. Healthy Indonesia Program Data with a Family Approach shows that only 46% of people with mental disorders in Yogyakarta receive care and treatment. Grhasia Hospital as a hospital with mental health specialization owned by the Special Region of Yogyakarta Government carried out an innovation based on digital technology which was named Grhasia Ready to Evacuate People with Mental Disorders (Grhasia Sadewa). Grhasia Sadewa is expected to facilitate access to referrals and reduce the length of the people with mental disorders evacuation process that has been carried out so far. Purpose: Determine the effect of Grhasia Sadewa on the response time of requests for people with mental disorders evacuation at Grhasia Hospital Yogyakarta. Methods: This study uses a quasi-experimental posttest-only design with a control group. The research participants were 64 users of people with mental disorders evacuation services at Grhasia Hospital in 2021-2022. Data were obtained secondary from service documentation at Grhasia Hospital. Data analysis using the Mann-Whitney test. Results: The mean response time to requests for evacuation for people with mental disorders in the group not using the Grhasia Sadewa application was 4924.60 minutes, while the mean for the group using the Grhasia Sadewa application was 373.43 minutes. The results of the Mann-Whitney Test show p value = 0.00 (less than 0.05) so it can be concluded that there is an effect of Grhasia Sadewa on the response time of requests for people with mental disorders evacuation at Grhasia Hospital Yogyakarta. Conclusion: The response time for evacuation requests for people with mental disorders is faster after Grhasia Sadewa is applied. Grhasia Sadewa needs to be socialized to the community and health centers in the Special Region of Yogyakarta to facilitate access to mental health services for the community.